Penggunaan Media Sosial sebagai Penunjang Pembelajaran Mata Pelajaran PPKn - Sulton Sulton; Ardhana Januar Mahardhani; Refita Refita; Susi Octavia (Proceedings Series of Educational Studies, 2023)
Social media education that can be implemented by students in the 21st century is by applying social media in learning. Educators must change students' mindsets regarding the purpose of using social media from just looking to becoming a place to learn. Make the aim of using social media in a positive direction and have an influence on student learning and learning outcomes. This research aims to determine the implementation of the use of social media as a means of supporting learning for class XI Science students at SMAN 3 Ponorogo. The method used is qualitative, the techniques used in collecting data are observation, interviews and documentation. The results obtained were that the implementation of learning in Civics subjects at SMAN 3 Ponorogo in realizing an independent curriculum utilized social media including WhatsApp, Instagram, Quizzy, TikTok, and also other supporting digital applications such as Google Meet, Google Classroom, Google Form, and Zoom